The conditional role of personal information-security norms in prosocial patient information disclosure among health professions students - Youngsoon Park; Kyunghee Chun (Korean Journal of Medical Education, 2026)
Purpose: This study examined whether perceived medical need for disclosure (PMND) predicts prosocial intention to disclose patient information (PI) among health professional students, and whether personal norms (PN) moderate this relationship. A particular focus was PN’s dual statistical role—its direct association with PI and its moderation of the PMND–PI association.Methods: A cross-sectional survey was administered to 210 undergraduate students at a single Korean university (116 medical, 42 nursing, 52 emergency medical services). Participants were randomly assigned to one of four scenarios (2×2: disease severity × information security environment). Four-step hierarchical regression and simple slope analyses tested the main and moderating effects.Results: PMND positively predicted PI (β=0.347, p